Barbastella barbastellus - Don E. Wilson; Russell A. Mittermeier (Lynx Edicions, 2019)
219. Western Barbastelle Barbastella barbastellus French: Barbastelle d'Europe / German: Mopsfledermaus / Spanish: Barbastela Other comesnon names: Barbastelle Taxonomy. Vespertilio barbastellus Schreber, 1774, Burgundy, France. Two subspecies are recognized. Subspecies and Distribution. B.b.barbastellusSchreber,1774—EuropefromIrelandandIberianPeninsulaEtoLaivia,Belarus,Ukraine,andtheCauca-sus;alsomajorMediterraneanIs,Moroc-co,andTurkey(Anatolia);possiblyextinctinBelgium,Netherlands,andNorway. B. b. guanchae Trujillo, Ibanez & Juste, 2002 — Canary Is (Tenerife and La Gomera). Descriptive notes. Head-body 45-60 mm, tail 36-52 mm, ear 12-18 mm, forearm 35-43 mm; weight 5-14 g. Females slightly larger than males; body slender. Fur is long, silky, and black-brown, frosted with white or yellowish-golden tips. Skin dark brown or grey. Juvenile much darker than adult. Ears have distinctive flap of skin (c.5-6 transverse folds) on outer edge; tragus triangular and very distinctive, tapering very abruptly to end with relatively rounded tip; ears never folded when resting. In contrast to Plecotus, eyes remarkably small. Wings blackish, relatively long and narrow; uropatagium attached to base of toes; fur covers part of both uropatagium and wings; calcar is one-half length of uropatagium and has protuberant distal postcalcarial lobe. Tail is almost same length as body. Can be confused with the Eastern Barbastelle (B. darjelingensis) and the Arabian Barbastelle (B. leucomelas), but easily separated by its short, wide trapezium-shaped ears that face forward and join over top of head, and its short snout. Baculum 0-76- 0-85 mm long, with broad section in proximal part and narrow section in distal area. Skull light and delicate, with long, rounded braincase but short rostrum, characterized by flattened area extending to not greatly developed supraorbital ridge; bullae are not very large compared to similar species. Condylo-basal length 12:4-14- 1 mm; zygomatic width 7-8- 2 mm; interorbital width 3:4- 3-9 mm; length of ...